Varieties of top incomes: Power, regulation and growth models - Mergulhão, A. (Comparative European Politics, 2025)
The recent shift within Comparative Political Economy, towards analysing the distributional implications of growth models through macroeconomic explanations, contrasts with the traditional focus on institutions and public policies. This paper examines 22 OECD cases using configurational methods (fsQCA) to analyse the necessary and the sufficient conditions for high- and low-income inequality. Results show that export-led growth only leads to high top 1% shares if employment protection legislations are weak. Similarly, the combination of consumption-led growth with financialization is not sufficient for elites to extract high shares, but rather is the simultaneous absence of unions’ associational power and labour legislation’s institutional power. Additionally, beyond these key power resources, and despite relatively low financialization, German and Spanish elites extract high shares through diminishing progressivity amid large-scale privatizations. On the other hand, most countries achieve low inequality through the combined regulation of labour and product markets. These findings reveal that agency over market regulations and workers' power remain at the centre of inequality dynamics, particularly at the top.